[ 11 C]Carfentanil PET Whole-Body Imaging of μ-Opioid Receptors: A First in-Human Study - Dubroff, Jacob G.; Hsieh, Chia-Ju; Wiers, Corinde E.; Lee, Hsiaoju; Schmitz, Alexander; Li, Elizabeth J.; Schubert, Erin K.; Mach, Robert H.; Kranzler, Henry R. (Journal of Nuclear Medicine, 2025)
μ-opioid receptors (MORs) are G-coupled receptors widely expressed in the brain and body. MORs have a high affinity for both endogenous opioids such as β-endorphins and exogenous opioids such as fentanyl. They mediate pain and reward and have been implicated in the pathophysiology of opioid, cocaine, and other substance use disorders. Using an instrument with a long axial field of view and the MOR-selective radioligand [ C]carfentanil, we measured the whole-body distribution of MORs in 13 healthy humans. We also examined sex differences in MOR distribution at baseline and after pretreatment with the MOR antagonist naloxone. Six female and 7 male healthy subjects underwent 2 [ C]carfentanil PET imaging sessions-one at baseline and one immediately after pretreatment with the MOR antagonist naloxone (13 μg/kg). Whole-body PET imaging was performed on an instrument with a 142-cm axial bore. [ C]carfentanil brain distribution volume ratios were determined using the occipital cortex and the visual cortex within it as reference regions. For peripheral organ distribution volume ratios, the descending aorta and proximal-extremity muscle (biceps/triceps) were used as reference regions. Naloxone blockade reduced MOR availability by 40%-50% in the caudate, putamen, thalamus, amygdala, and ventral tegmentum, brain regions known to express high levels of MORs. Women showed greater receptor occupancy in the thalamus, amygdala, hippocampus, and frontal and temporal lobes and a greater naloxone-induced reduction in thalamic MOR availability than men ( < 0.05). For determining brain MOR availability, there was less variance in the visual cortex than in the occipital cortex reference region. For peripheral MOR determination, the descending aorta reference region showed less variance than the extremity muscle, but both showed blocking effects of naloxone. [ C]carfentanil whole-body PET scans are useful for understanding MOR physiology under both baseline and blocking conditions. Extra-central nervous system reference regions may be useful for quantifying radiotracers when a region devoid of binding in the central nervous system is unavailable. The long axial field of view was useful for measuring changes in the short-lived radiotracer [ C]carfentanil, with and without naloxone blocking. Further research is needed to evaluate the behavioral and clinical relevance of sex differences in naloxone-MOR interactions.